Use of resistance inducer associated with different fungicides in soybean (Research, Society and Development, 2022)
Phytoalexins are a group of chemically diverse, antimicrobial, low molecular weight secondary metabolites with strong antimicrobial activity that accumulate around the site of infection. Based on the hypothesis that the use of resistance inducers associated with fungicide application promotes greater control of diseases in soybean, the objective of this study was to quantify the incidence and severity of diseases as a function of the use of resistance inducers associated with application. of fungicide in the soybean crop. The experiment was developed in the experimental area belonging to the company Tecno Nutrição Vegetal e Biotecnologia Ltda. The experimental design used was randomized blocks with four replications. The treatments consisted of the application of 5 combinations of biostimulants: T1) Fox (45; 65; and 85 DAP); T2) Fox + Fitalexy (45 DAP), Fox (65 and 85 DAP); T3) Fox + Fitalexy (45 and 65 DAP) and Fox (85 DAP); T4) Priori Xtra (45, 65 and 85 DAP); T5) Priori Xtra + Fitalexy (45 DAP) and Priori Xtra (65 and 85 DAP); T6) Priori Xtra + Fitalexy (45 and 65 DAP) and Priori Xtra (85 DAP); T7) Approach Prima (45, 65 and 85 DAP); T8) Approach Prima + Fitalexy (45 DAP) and Aproach Prima (65 and 85 DAP); T9) Prima Approach + Fitalexy (45 and 65 DAP) and Control. The variables severity of diseases and soybean grain yield were measured. Data were submitted to analysis of variance (p